Comparison of effectiveness of intubation by way of "Gum Elastic Bougie" and "Intubating Laryngeal Mask Airway" in endotracheal intubation of patients with simulated cervical trauma - Sut,Esra Yildiz (2017)
Abstract Purpose: In this study, we evaluated the effectiveness of intubations by way of "Gum Elastic Bougie" and "Intubating Laryngeal Mask Airway" in endotracheal intubation of patients with simulated cervical trauma. Method: 134 patients were included in the study. All patients were placed cervical collar for a simulated cervical trauma. Patients were allocated randomly into three groups: Group NI (n = 45) intubation with Macintosh laryngoscopy, Group GEB (n = 45) intubation with Gum Elastic Bougie, and Group ILMA (n = 44) intubation with Intubating Laryngeal Mask Airway. The number of intubation attempts, success of intubation, duration of complete visualization of the larynx, duration of intubation, user's performance score, hemodynamic changes and the observed complications were recorded. Results: Success of intubation in the first attempt was highest in Group GEB while it was lowest in Group ILMA. Regarding the intubation success, rates of successful intubation were 95.6%, 84.4% and 65.9% in Groups GEB, NI, and ILMA, respectively. Durations of visualization of larynx and intubation were shorter in Groups NI and GEB than in Group ILMA. This difference was statistically significant (p < 0.05) while there was no significant difference between Groups NI and GEB. The number of patients with "good" intubation performance was significantly higher in Group GEB while the number of patients with "poor" intubation performance was significantly higher in Group ILMA (p < 0.05). Conclusions: We conclude that GEB, which is cheap and easily accessible, should be an advantageous choice in cervical trauma patients for both the easeness of intubation and patient morbidity and mortality.